Analisis Signifikansi Roda Skateboard Berbahan Komposit Serbuk Batang Pisang Terhadap Perfoma Kecepatan Dengan Metode Anova - Achmad Jusuf Zulfikar; Muhammad Yusuf R. Siahaan; Ruli Bay Syahputra (Rekayasa Material, Manufaktur dan Energi, 2021)
In general, skateboard wheels are made from a mixture of polyurethane (PU) so that they are elastic, lightweight, and strong. However, this material is classified as a toxic material, difficult to obtain, and the price is relatively expensive. Therefore, alternative raw materials that are more environmentally friendly, non-toxic, easy to find, and have sufficient availability are needed. Banana trees are the most abundant and easily found plants in Indonesia, especially Medan. This tree has a soft structure and absorbs vibrations. Thus, the research was conducted to obtain the characteristics of skateboard wheel products from banana stem powder (SBP) composite material as an alternative raw material. The purpose of this study was to analyze the speed of skateboards made of PU (commercial) and SBP in order to obtain the optimum composition of SBP for the manufacture of skateboard wheels. The test uses a sliding platform with a slope of 30o against a flat plane. The number of variations consists of the composition of SBP 5%, 10%, and 15%. As a control, commercial PU wheels were also tested. Analysis of data using the analysis method of mean variation (ANOVA) with the condition of acceptance of the hypothesis H0 at a 0.05. The results obtained are that there is an increase in the speed of skateboards made of SBP composite up to 6, 85% compared to commercial wheels. Based on the Anova test results, it was found that the application of SBP composite materials as raw material for skateboard wheels was proven to significantly increase the speed performance of these wheels.